The Effect of Red Beetroot Juice (Beta vulgaris, sp.) on the Tooth Color - Selviana Wulansari; Gabriela Lintang Cristandy; Tien Suwartini (Journal of Indonesian Dental Association, 2019)
Introduction: Tooth discoloration is one of the problems and the reason why people begin to notice the appearance of their teeth. Phenolic compounds are often found in foods and beverages, one of them is red beetroot juice that cause discoloration on the tooth surface. The acidity of red beetroot juice is a factor of color changes on the tooth surface extrinsicly. Objectives: This study aims to determine the effect of red beetroot juice on color changes of tooth surface. Methods: This experimental laboratory research conducted pretest and posttest. Twenty maxillary premolar samples within inclusion criteria were stored in the artificial saliva at 37oC and treated for 30 minutes using 50 mL red beetroot juice, followed by immersion in artificial saliva overnight. Treatment was repeated 7 times for 7 days consecutively. The teeth was tested by using Vita Easyshade V before and after treatment and then the acquired data was statistical tested using paired T-test. Result: T-test showed variable E, C and H with p=0.000 (p<0.05) showed a significant changes in total color deviation, chroma and hue, while the variable of L with p=0.015 (p>0.05) meant no significant change of value. Conclusion: It can be concluded that red beetroot juice (Beta vulgaris, sp) can affect color changes on the tooth surface.